2016
DOI: 10.1177/0886260516645575
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Experiences of Abuse and Harassment in Emergency Departments

Abstract: The widespread epidemic of emerging abuse in Emergency Departments (ED) toward residents generates negative effects on the residents' health and welfare. The purpose of this study was to determine and highlight the high prevalence of abuse and harassment toward Emergency residents. In 2011, a multi-institutional, cross-sectional study was conducted at seven Emergency Residencies of central hospitals in Iran. Residents were asked about their age, marital status, postgraduate year (PGY) levels, and work experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
5
11
1
1
Order By: Relevance
“…We found that the main perpetrators of workplace violence were other workers of the institution, followed by patients/relatives. Similar results have been reported in other studies in Turkey [14], Iran [13], Japan [15], Uruguay [17], Argentina [19], Mexico [29], and Venezuela [30]. However, studies in the United States [7] and Mexico [16] found that aggressors were mainly patients/relatives.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that the main perpetrators of workplace violence were other workers of the institution, followed by patients/relatives. Similar results have been reported in other studies in Turkey [14], Iran [13], Japan [15], Uruguay [17], Argentina [19], Mexico [29], and Venezuela [30]. However, studies in the United States [7] and Mexico [16] found that aggressors were mainly patients/relatives.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of workplace violence was 73.4%, similar to that reported in studies in the United States [7, 8], Iran [12, 13], Turkey [14], Japan [15], Argentina [19], Mexico [29], and Venezuela [30], in which the prevalence ranged from 66% to 97%. In addition, we found that verbal violence was more frequent than physical violence (72.7% vs 16.3%), similar to other studies conducted in different populations of residents [3, 7, 8, 1315, 19, 31]. It is important to note that both physical and verbal violence can have a negative impact on the resident's emotional, academic, and professional status [32].…”
Section: Discussionsupporting
confidence: 80%
“…A significant association was found between the resident's doctor's young age and exposure to verbal violence. This finding is in line with a previous report [36], and could be attributed to the fact that senior resident doctors have better communication skills and are more professional in dealing with nervous and agitated clients. Also, this patient-initiated violence might be due to the lack of medical management skills by junior resident doctors and the respect of patients for an older doctor.…”
Section: Prevalence and Characteristics Of Wpv Against Resident Doctosupporting
confidence: 93%
“…It was also notable that many of the men had overheard their male colleagues making inappropriate comments about female physicians' physical appearance. These reports of witnessed harassment are consistent with the previous literature suggesting that gender-based harassment and sexual harassment are common in medicine 1,2,12,13 . They are also consistent with our previous qualitative work with women in which, universally, the women reported experiencing some form of sexual or gender-based harassment 11 .…”
Section: Discussionsupporting
confidence: 91%